PROBLEMS OF FINDING INTEGRAL REPRESENTATIONS OF SOME GENERELIZED HYPERGEOMETRIC FUNCTIONS (Scientific journal of the Fergana State University, 2023)
This article examines the problem of finding the integral representation of some generalized hypergeometric functions.